My grandmother asked me to tell you she's sorry : a novel - Backman, Fredrik, 1981- (Atria Books, 2015)
"From the author of the internationally bestselling A Man Called Ove, a charming, warmhearted novel about a young girl whose grandmother dies and leaves behind a series of letters, sending her on a journey that brings to life the world of her grandmother's fairy tales"--